2005
DOI: 10.1521/suli.2005.35.5.558
|View full text |Cite
|
Sign up to set email alerts
|

Factors Associated with Suicide Attempts in Female Inmates: The Hegemony of Hopelessness

Abstract: In this study factors associated with past suicide attempts in female inmates were examined. Female inmate participants (N = 105) were given structured diagnostic assessments of antisocial and borderline personality disorders and substance dependence, as well as measures of depression, hopelessness, problem-focused coping styles, and reasons for living. There was a high lifetime prevalence of past suicide attempts (38.1%). Suicide attempts were positively associated with personality disorders, hopelessness, de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
85
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(91 citation statements)
references
References 39 publications
5
85
0
1
Order By: Relevance
“…As perceived burdensomeness and thwarted belongingness are necessary mental states involved in the development of perceived burdensomeness and thwarted belongingness, this result partially supports findings by Horowitz, Hill, and King [13] that behavioral disengagement is associated with suicide risk. The items comprising the behavioral disengagement subscale (e.g., "I've been giving up trying to deal with it" and "I've been giving up the attempt to cope") raise the possibility that this coping behavior may be a response to feelings of hopelessness, which has been well documented as a predictor of suicidal ideation ( [6,12,33]). However, it should be noted that some subscales demonstrated lower internal consistency than desired.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As perceived burdensomeness and thwarted belongingness are necessary mental states involved in the development of perceived burdensomeness and thwarted belongingness, this result partially supports findings by Horowitz, Hill, and King [13] that behavioral disengagement is associated with suicide risk. The items comprising the behavioral disengagement subscale (e.g., "I've been giving up trying to deal with it" and "I've been giving up the attempt to cope") raise the possibility that this coping behavior may be a response to feelings of hopelessness, which has been well documented as a predictor of suicidal ideation ( [6,12,33]). However, it should be noted that some subscales demonstrated lower internal consistency than desired.…”
Section: Discussionmentioning
confidence: 99%
“…Across a broad range of populations, the relationship between coping and suicide has been examined with mixed results [12][13][14][15]. Some coping strategies, such as seeming emotional support and attempting to think about solutions to a specific problem, have been shown to be inversely associated with suicidal ideation and behavior (e.g., [13,14]).…”
mentioning
confidence: 99%
“…In a study conducted with 40 substance-dependent incarcerated women, Peltan and Cellucci [25] found that most of the women also reported some type of childhood abuse. In another study [26], 78 % of the 105 female inmates studied reported childhood physical/emotional abuse, 59 % reported sexual abuse, and 38 % reported neglect. Furthermore, Green et al [27] found childhood trauma and other interpersonal traumas in a sample of female inmates, with 62 % reporting exposure to childhood trauma and 90 % reporting the experience of at least one interpersonal trauma.…”
Section: Gender Differences In Childhood Abuse Among Inmatesmentioning
confidence: 93%
“…Esse mesmo alto percentual foi encontrado em outro estudo 17 , o qual denota que 61,7% das mulheres reclusas apresentaram depressão ao longo da vida. Já outra pesquisa, em que foi aplicado o BDI II, apontou 18% de prevalência de sintomas depressivos clinicamente significativos e 68,6% apresentando disforia 18 .…”
Section: Associação Entre Variáveis E Sintomas Depressivosunclassified